Temperature and Humidity Monitoring System in Internet of Things-based Solar Dryer Dome - Anton Yudhana; Dzakarasma Tazakka Ma’arij (Universitas Ahmad Dahlan, 2023)
The village of Gerbosari has a program for cultivating spice rhizome plants as an effort to improve the economy. These plants are dried using a Solar Dryer Dome (SDD) as a solution to the rain-related issues. The SDD has an automatically controlled exhaust fan based on the measured temperature. Temperature and humidity readings are taken using DHT22 and DHT11 sensors, respectively. Weather conditions (clear or rainy) are detected using a rain sensor. Weather, temperature, and humidity monitoring are done through On The Spot (OTS) and Internet of Things (IoT) methods. OTS utilizes an LCD 16x2, while IoT utilizes the Blynk application and WhatsApp. The temperature errors for DHT22 and DHT11, respectively, are 1.572% and 0.721%, while the humidity errors are 5.223% for DHT22 and 3.214% for DHT11. If the error values approach 5% or more, program adjustments are necessary. Throughout the day, regardless of clear or rainy weather, the temperature inside the SDD is higher, and the humidity is lower than the temperature and humidity outside.